Sex-Specific Genetic Data Support One of Two Alternative Versions of the Foundation of the Ruling Dynasty of the Nso' in Cameroon. - Veeramah, K; Zeitlyn, D; Fanso, V; Mendell, N; Connell, B; Weale, M; Bradman, N; Thomas, MG (University of Chicago Press, 2008)
Sex-specific genetic data favor a specific variant of the oral history of the kingdom of Nso' (a Grassfields city-state in Cameroon) in which the royal family traces its descent from a founding ancestress who married into an autochthonous hunter-gatherer group. The distributions of Y chromosome and mitochondrial DNA variation in the Nso' in general and in the ruling dynasty in particular are consistent with specific Nso' marriage practices, suggesting strict conservation of the royal social class along agnatic lines. This study demonstrates the efficacy of using genetics to augment other sources of information (e.g., oral histories, archaeology, and linguistics) when seeking to recover the histories of African peoples.